ЕНЕРГЕТИЧНИЙ ПОТЕНЦІАЛ НАСАДЖЕНЬ ГОЛОВНИХ ЛІСОУТВОРЮВАЛЬНИХ ПОРІД ПІВНІЧНОГО СТЕПУ УКРАЇНИ - Sytnyk, S. A.; Lovynska, V. M. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2018)
Introduction Tree phytomass is one of the few environmentally friendly types of fuel and renewable energy sources. It doesn’t transform the gas balance of the atmosphere and doesn't accelerate the global climate change. Trees biomass energy using in Ukraine contributes to substantial savings of own fossil fuels, reduction imports and cheapening of energetic resources.  Moreover such using of wood biomass conduces to the increase of the forest covered area of the country due to the creation of new forests and energy plantations. The aim of the study is to assess the energy potential of black locust and pine plantations in the Northern Steppe of Ukraine by the determination of the components of the stand aboveground phytomass and the carbon sequestration. Materials and Methods Temporary sample plots in black locust (Robinia pseudoacacia L.) and Scots pine (Pinus sylvestris L.) stands were established to study components of aboveground plant phytomass within Northern Steppe of Ukraine. The research of aboveground phytomass in the modal black locust and Scots pine forests was carried out by a special method (Lakyda, 2003). To evaluate the carbon content and the accumulated energy in the phytomass the averaged scientific data were used, which state that the average ratio of carbon in one ton of wood biomass (wood, bark) is 0.50, and for the fraction of the leaves (needles) it is 0.45. Results Within Northern Steppe, black locust stands have soil protection functions; they occupy the area of 17,683.7 ha (i. e. 26.9 % of the area covered by forest vegetation) with the total growing stock of 2,624.81 thousand m?. Pine forest stands perform main recreation functions and occupy the area of 21,472.9 hа (or 32.5 % of the area covered by forest vegetation) with total growing stock of 4,571.1 thousand m3. The total carbon stock in the forest stands of main species is 2,034.34 thousand ton, 1134.14 thousand ton of which is in pine stands and 900.20 is in black locust stands. In the black locust stands, the share of accumulated carbon in stem bark and branches is twice higher than that in such fractions of aboveground phytomass of pine stands. Totally, the major portion of organic carbon is accumulated in the phytomass of stem wood and the lowest one is in needles and leaves. The aboveground phytomass of forest stands of the Northern Steppe of Ukraine is 4,118.55 thousand ton. The aboveground phytomass of the black locust stands amounts to 1,841.97 thousand ton the carbon stock of which is 900.20 thousand ton. The pine stands have 2,276.58 thousand ton of the aboveground phytomass that sequester 1134.34 thousand ton of carbon. The energy potential of black locust stands of the Northern Steppe of Ukraine is 32,188.14 GJ, whereas this index for Scots pine is 40,556.84 GJ. With regard to the component structure of the aboveground phytomass, wood trunks have the highest energy potential both for Scots pine and black locust. Conclusions The results of the evaluation of the aboveground phytomass components, sequestered carbon and stored energy in black locust and pine stands of the Northern Steppe of Ukraine reflect the current characteristics of the environmental and energy potential of the studied forest stands.